2012
DOI: 10.1111/j.1600-0447.2012.01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic events and suicidal behaviour in the Nigerian Survey of Mental Health and Well‐Being

Abstract: Traumatic events are common in the general population. This report highlights the role of traumatic events (especially those related to violence) in predicting suicidal behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
4
8
0
Order By: Relevance
“…In this study, NLEs had higher incidence in suicide attempters than in controls across all four time periods. We also found a dose-response relationship between number of NLEs and attempted suicide, consistent with previous studies [ 8 , 31 33 ]. As a risk factor, NLEs may directly cause attempted suicide as a solution or avoidance of the difficulties and stress derived from them, or indirectly facilitate the behavior by generating and aggravating psychiatric symptoms [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, NLEs had higher incidence in suicide attempters than in controls across all four time periods. We also found a dose-response relationship between number of NLEs and attempted suicide, consistent with previous studies [ 8 , 31 33 ]. As a risk factor, NLEs may directly cause attempted suicide as a solution or avoidance of the difficulties and stress derived from them, or indirectly facilitate the behavior by generating and aggravating psychiatric symptoms [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…This loss of association seen in the final multivariate model suggests that other factors, such as personality dimensions and psychiatric disorders, have a mediating and/or moderating effect on suicidality [ 46 48 ], attenuating the correlation between childhood adversity and suicidality. Similar results were obtained in a worldwide cross-national survey [ 7 ], as well as in studies conducted in underdeveloped countries such as South Africa and Nigeria [ 49 ] [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…One example of such bias could be the low prevalence of sexual abuse, which suggests under-reporting. In the present study, the rates of sexual abuse were low and were comparable to those reported in studies conducted in South Africa (0.7–2.1%), Nigeria (1.4 to 4.8%), Lebanon (0.4%), and Japan (0.5%) [ 49 , 50 , 59 , 60 ], all of which used methodologies analogous to that used here. That might have resulted in an underestimation of the association between childhood adversities and suicidality.…”
Section: Discussionsupporting
confidence: 86%
“…The services are often located in cities and primary care workers are overburdened, and have insufficient skills or experience in mental health care [ 6 ]. Additionally, people with mental illness often face discrimination, are inappropriately incarcerated, and denied economic, social and human rights [ 7 , 8 ]. The local language used to conceptualize mental illness may be dismissive and contribute to the stigma of mentally ill patients.…”
Section: Introductionmentioning
confidence: 99%